O investimento na carreira futebolística de jovens mulheres: um estudo etnográfico - Mion, Maria Paula Louzada (2023)
The women's soccer scene is undergoing significant transformations at national, continental and global level. In 2019, the requirement for Brazilian clubs to have women's teams, both adult and grassroots, triggered a process of professionalization of women's soccer and boosted the formation of a footy market in the country. Given this scenario, we asked ourselves: how are young women, immersed in the process of investing in their sporting careers, experiencing, perceiving and integrating with these recent changes in the national soccer context? How do these transformations affect the construction of meanings in the dream of being a soccer player? The aim of this research was to understand the meanings that mobilize young women to invest in a sports career in soccer. Based on an ethnography carried out at a sports exchange academy located in the municipality of Serra/ES, we spent 15 months with approximately 40 young women aged between 13 and 27. Training sessions took place on Saturdays and lasted approximately two hours. The results showed that there is a market for crowbars which is still being consolidated. In their desire to be part of this market, the young aspiring players come to the academy with different objectives for a life or career project related to women's soccer. In the daily life of the institution, boarding is a term used to refer to the movement to migrate to other institutions - whether national or international, club or academic - to play soccer. In this universe, even if they dream of going to the shop windows of this new soccer market, the history of the sport in Brazil means that strategies must be intelligently developed by the academy, so that both the young women and those responsible for such investments can see a promising future in this circuit. Becoming part of the footy market, in this scenario, is a movement that involves constant tension and negotiation in the quest to demystify the dream of professionalization from the plane of utopia and to be able to experience a soccer career in an optimistic and promising scenario.